Mosques and madrasas in the Northern Kazakhstan at the end XX - early XXI centuries - Mustafina, R. M. (Journal of Oriental Studies, 2016)
The materials of the ethnographic research revealed, that the religious life in the Northern-Kazakhstan region that period was not active even despite the missionary activity of the foreign theologies. The shortage of religious institutions and the well educated Muslim clergy in villages promoted the low level of religiosity of believers in rural region. Self-made mulla (representative of the Muslim clergy) wаs not the rare phenomena that time. Nevertheless the general tendencies of increasing of the role of Islam in Kazakhstan infl uenced on the religious life in the Northern Kazakhstan region.